(untitled) (The International Journal for Scientific Research, 2024)
This survey study aims to reveal the Jordanian citizens’ opinions about Syrian Asylum and the ongoing existence of Syrians refugees in Jordan, and the impact of the Syrian Asylum on the variant sectors of Jordan. The leading argument of this study assumes that there has been a significant negative impact of Syrian Asylum on the economic, social and security aspects of the Jordanian society, and this has posed additional economic, social, and security challenges for Jordan. For the purpose of this survey study, the descriptive analytical approach was adopted. David Easton’s systems analysis framework was also used for the sake of analysis. To collect data from primary sources, a questionnaire was developed and distributed to a random sample of 500 cases. The study attained a number of results, the most significant of which are as follows: 1. Most Jordanians believe that the presence of Syrian refugees in Jordan causes many problems for Jordanian society and places heavy burdens on the country’s economy, and that the resettling of the Syrian refugees to their country will help to resolving many of the challenges help Jordanian society. 2. The majority of Jordanians prefer the return of Syrian refugees to their homeland in light of the decline of the Syrian crisis. Based on these results, the study introduces a number of important recommendations: 1. Dismissing the idea of integrating Syrian refugees into Jordanian society, as advocated by some international organizations. 2. Maintaining security along the Jordanian border to stop the flow of weapons and preventing the leakage of any weapons, military groups, or smuggled vehicles in both directions, Additionally, the government of Jordan and other nations, like the Gulf States, are concerned about drug smuggling operations.